2019
DOI: 10.1021/acs.jpcb.9b09269
|View full text |Cite
|
Sign up to set email alerts
|

Giant Axial Dielectric Response in Water-Filled Nanotubes and Effective Electrostatic Ion–Ion Interactions from a Tensorial Dielectric Model

Abstract: Molecular dynamics simulations in conjunction with effective medium theory are used to investigate dielectric effects in water-filled nanotubes. The resulting effective axial dielectric constant shows a divergent increase for small nanotube radii that depends on the nanotube length, while the effective radial dielectric constant decreases significantly for thin nanotubes. By solving Poisson's equation for an anisotropic dielectric medium in cylindrical geometry, we show that the axial ion-ion interaction depen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 59 publications
3
44
0
Order By: Relevance
“…Our results agree qualitatively with recent theoretical findings reported by Loche et al [38] for carbon nanotubes. Some quantitative differences might be attributed to a more rigorous formalism employed by the authors [38] …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Our results agree qualitatively with recent theoretical findings reported by Loche et al [38] for carbon nanotubes. Some quantitative differences might be attributed to a more rigorous formalism employed by the authors [38] …”
Section: Resultssupporting
confidence: 94%
“…The authors found that water confined in 10 nm gaps exhibits an anomalous low ϵopt (1.57), which is even lower than for hexagonal ice (1.625). In general, the reorganization energy should be reduced taking into account solvent quantum modes (for bulk water, e. g., a reduction by about 20 % is found [38] ). We did not address, however, this additional effect.…”
Section: Resultsmentioning
confidence: 99%
“…The free energy ∆G φ will also depend on surface geometry, whereby the dielectric profiles can differ markedly between planar and curved geometries, along with the long-range electrostatic ion-ion interactions. 74,75…”
Section: Resultsmentioning
confidence: 99%
“…Third, the dielectric function is inhomogeneous, with position dependence which is non-trivial, as also discussed by others. 9,10 Let us discuss these issues for the specic problems at hand. For a cylindrical specimen placed in a Cartesian coordinate system, we have two unique non-zero eigenvalues dening the dielectric tensor -(i) axial dielectric constant (3 z ) that arises due to an electric eld that is parallel to the axis of the cylinder, and (ii) a perpendicular dielectric constant (3 x ¼ 3 y ¼ 3 x/y ) that arises due to an electric eld that is perpendicular to the principle axis of the cylinder.…”
Section: Issues With the Theoretical Formalism Used By Zhu Et Almentioning
confidence: 99%
“…Additionally we discuss another different approach to obtain the spatially resolved axial and radial dielectric proles for dipolar uids inside nano-cylindrical connement. 10,14 It can be shown that for a cylindrical system E(r) is xed along the Z direction and rD(r) is xed along the radial direction; where D(r) is the radially varying electric displacement eld. By employing linear response theory one can derive the following two equations [eqn (12) and ( 13)].…”
Section: Correct Linear Response Equationsmentioning
confidence: 99%